Variables influencing telemedicine utilization via telephone appointments among rural patients - Eliseo García; Benjamin C. Vincent; Shivani Thakur; Ashish Thakur; Fatima Zabiba; Sandhini Agarwal; Jasmin Dominguez Cervantes; Ahmed Zabiba (BMC Health Services Research)
Abstract Objective To evaluate patient preferences when utilizing telemedicine. Methods A 5-point Likert scale questionnaire was completed by 153 patients at a rural clinic via a convenience sampling method. The survey contained 21 statements encompassing provider confidence, patient-physician rapport, and accessibility variables. Patient responses for those who attended (n = 120) or canceled/rescheduled (n = 33) telemedicine encounters were analyzed using paired difference t-tests and t-tests of correlations between different groups of variables. An ad-hoc method patterned after the least significant differences was applied to the analysis of variance results to evaluate patient-valued variables. Results Patients surveyed included 82.4% female (n = 127) and 17.6% male (n = 26); 69.3% of them were Hispanic/Latino (n = 106). When reviewing the patient opinion statements, our data suggested a belief that telemedicine encounters were as good as in-person visits (n = 118, x̄ = 4.932) and that such encounters provided them with the confidence to proceed with future, in-person vein treatments (n = 117, x̄ = 4.744). Additionally, patients expressed feeling as though their personal information was safe (n = 117, x̄ = 4.897). Conclusion Rural patients indicated a preference for flexible encounters and for providers who strive to build trust and rapport when utilizing telemedicine.